Wild Piper species from Vietnam and Laos with genetic diversity, Phytophthora capsici resistance, and eugenol-rich chemotypes - NHI THI HOANG HO; HAN NGOC HO; HAI THI HONG TRUONG (Society for Indonesian Biodiversity, 2026)
Abstract. Ho NTH, Ho HN, Truong HTH. 2026. Wild Piper species from Vietnam and Laos with genetic diversity, Phytophthora capsici resistance, and eugenol-rich chemotypes. Biodiversitas 27 (4): d270427. https://doi.org/10.13057/biodiv/d270427. Black pepper (Piper nigrum) is an economically important spice, but its productivity is severely constrained by Phytophthora capsici. Wild Piper species represent a valuable genetic resource for improving disease resistance and exploring bioactive compounds; however, the knowledge about them remains insufficiently characterised. This study aimed to evaluate the genetic diversity of wild Piper accessions collected from Vietnam and Laos, assess their resistance to P. capsici, and analyse leaf chemical composition associated with resistance. Genetic diversity was examined using the ITSu1-4 region and RAPD markers, while resistance was evaluated through in vitro detached-leaf assays. Chemical profiling of selected accessions was performed using GC-MS analysis. The ITS analysis identified four species, including Piper betle, Piper pendulispicum, Piper thomsonii, and Piper tricolor. The inclusion of wild accessions increased overall genetic diversity within the studied population, and RAPD analysis revealed high polymorphism, separating the accessions into three distinct clusters. Chemical analysis indicated that accessions resistant to P. capsici contained high proportions of eugenol and methyl eugenol, suggesting a relationship between resistance and eugenol-rich chemotypes. Although limited by sample size and the use of detached-leaf assays, the findings highlighted the potential of wild Piper germplasm as a genetic resource for breeding programs and as a source of natural compounds for biological control of P. capsici.